2010
DOI: 10.1002/esp.2042
|View full text |Cite
|
Sign up to set email alerts
|

Vegetated filter effects on sedimentological connectivity of agricultural catchments in erosion modelling: a review

Abstract: The sedimentological connectivity of agricultural catchments may be affected by anthropogenic structures (land management practices) established to reduce sediment exportation from agricultural plots to water streams. Distributed erosion models may in theory provide information about where and how these structures should be installed in catchments to reduce sediment exportation. The interaction between sediment exportation and land management practices is very complex from both theoretical and experimental poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 107 publications
3
69
0
7
Order By: Relevance
“…We assumed that similar characteristics influence sedimentation within ditches. As mentioned above, vegetation generates friction and roughness, which decrease the flow velocity and enhance the sedimentation potential (Fiener and Auerswald 2003;Gumiere et al 2011;Hösl et al 2012;Needelman et al 2007), which has been evidenced by Moore et al (2010), who detected a lower proportion of suspended solids in the water column of a vegetated ditch than those in the water column of a non-vegetated ditch. The ditch morphology and the water level fluctuations also influence the flow velocity .…”
Section: Sediment Retention In Ditchesmentioning
confidence: 89%
See 2 more Smart Citations
“…We assumed that similar characteristics influence sedimentation within ditches. As mentioned above, vegetation generates friction and roughness, which decrease the flow velocity and enhance the sedimentation potential (Fiener and Auerswald 2003;Gumiere et al 2011;Hösl et al 2012;Needelman et al 2007), which has been evidenced by Moore et al (2010), who detected a lower proportion of suspended solids in the water column of a vegetated ditch than those in the water column of a non-vegetated ditch. The ditch morphology and the water level fluctuations also influence the flow velocity .…”
Section: Sediment Retention In Ditchesmentioning
confidence: 89%
“…If gullies are connecting the adjacent field and the ditch, the sediment loads in the overland flow can reach very high concentrations (Lecce et al 2006;Tucker and Bras 1998). However, if ditches are connected to the adjacent fields by intact grass strips, the sediment loads may be consistently attenuated before reaching the ditch (Gumiere et al 2011;Huang et al 2002;Tucker and Bras 1998). Sidewall erosion is deemed to be a minor source of suspended sediments that are transported throughout vegetated ditches (Lecce et al 2006).…”
Section: Ditch Network: Pollutant Collectors and Propagation Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported trapping effectiveness was lower than the Iowa study: 15% to 23% for runoff, 28% to 30% for sediment, and 22% to 26% for TP loads over five years. These two unique field-scale studies document the potential for significant variation in the performance of upland buffers, possibly due to variations in slope, vegetation density, flow rate, soils, buffer width, and placement characteristics (Gumiere et al, 2011). From a literature review, Gumiere et al (2011) concluded that sediment removal was maximized when vegetated buffers were placed at the downstream edge of agricultural fields, close to the outlet.…”
mentioning
confidence: 99%
“…These two unique field-scale studies document the potential for significant variation in the performance of upland buffers, possibly due to variations in slope, vegetation density, flow rate, soils, buffer width, and placement characteristics (Gumiere et al, 2011). From a literature review, Gumiere et al (2011) concluded that sediment removal was maximized when vegetated buffers were placed at the downstream edge of agricultural fields, close to the outlet. The use of models to evaluate the effects of spatial organization of buffers is essential, as field experimentation for such evaluations is very expensive and difficult to apply.…”
mentioning
confidence: 99%